The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.12928/dpphj.v15i2.4748
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Children Under Five Years in the Work Area of Puskesmas Cipadung

Abstract: Background: Children under five years are in the golden growth and development period; however, an excellent nutritional status must support optimal growth and development. The nutritional status of children under five years needs special attention. An overview of the nutritional status of children in a region is the first step to determine the factors that affect the nutritional status of children under five in that region. Method: This was a descriptive study with a cross-sectional design. Results: The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
0
0
1
Order By: Relevance
“…They were also lower when the data were collected during the COVID-19 pandemic. Similarly, previous research has shown that significant factors associated with children's stunted growth include food insecurity [75,77], and not having a permanent place of residence [78]. Overall, reviews of the existing literature regarding growth delays among children aged under five years indicate that the most important socio-economic contributing factors are (i) parents' (and especially mothers') low education, (ii) low household income, (iii) food insecurity, and (iv) living in marginalized and deprived areas.…”
Section: Discussionmentioning
confidence: 92%
“…They were also lower when the data were collected during the COVID-19 pandemic. Similarly, previous research has shown that significant factors associated with children's stunted growth include food insecurity [75,77], and not having a permanent place of residence [78]. Overall, reviews of the existing literature regarding growth delays among children aged under five years indicate that the most important socio-economic contributing factors are (i) parents' (and especially mothers') low education, (ii) low household income, (iii) food insecurity, and (iv) living in marginalized and deprived areas.…”
Section: Discussionmentioning
confidence: 92%
“…Penentuan status gizi tergambar dari ketercukupannya penyediaan zat gizi serta dapat diserap oleh tubuh dengan optimal. Status gizi balita perlu mendapat perhatian khusus, gambaran status gizi balita di suatu wilayah merupakan langkah awal untuk mengetahui faktor-faktor yang mempengaruhi status gizi balita di wilayah tersebut (Nafia et al, 2021). Status gizi merupakan keseimbangan dari proses pemasukan dan pengolahan zat makanan oleh tubuh.…”
Section: Pendahuluanunclassified
“…Ketidakseimbangan gizi dalam tubuh anak akan menimbulkan masalah gizi yaitu masalah gizi kurang ataupun masalah gizi lebih. Di Indonesia, status gizi anak dibawah 5 tahun dimana yang menderita stunting sebesar 30,8%, prevalensi anak kurus dan sangat kurus sebesar 10,2% sedangkan untuk anak dengan status gizi gemuk sebesar 8% [4]. Pertumbuhan serta perkembangan terjadi peningkatan yang cepat pada usia 0 sampai dengan 5 tahun.…”
Section: Pendahuluanunclassified
“…Pertumbuhan serta perkembangan terjadi peningkatan yang cepat pada usia 0 sampai dengan 5 tahun. Usia ini merupakan "Golden Age" karena pada usia ini terbentuk dasar-dasar kemampuan indra, berpikir, berbicara dan pertumbuhan mental intelektual yang intensif [4] [5]. Golden age adalah masa tumbuh kembang anak yang sangat penting untuk diperhatikan secara detail agar jika timbul suatu kelainan dapat segera terdeteksi lebih awal [5].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation